Put do pobjede na izborima / The Path to Winning the Election: O aktualnosti antičkih savjeta u moderno doba / About Actuality of Ancient's Advice in Modern Age - Hebib, Mirza (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
A review of the book edited by Ivana Jaramaz Reskušić and Samir Aliĉić, Kvint Tulije Ciceron, Izborni priručnik sa govorima Marka Tulija Cicerona o izbornoj korupciji (University Press, Sarajevo, 2018, pg. 171).